2018
DOI: 10.1177/1591019918761640
|View full text |Cite
|
Sign up to set email alerts
|

Targeted endovascular treatment of haemorrhagic posterior fossa proliferative angiopathy

Abstract: Cerebral proliferative angiopathy (CPA) is a rare vascular abnormality and separate from “classical” brain arteriovenous malformations. Haemorrhage due to proliferative angiopathy is rarely reported. We describe the clinical features, imaging findings and targeted endovascular management for a 12-year-old boy having proliferative angiopathy of the posterior fossa presenting with haemorrhage. Targeted endovascular embolisation in CPA is not previously described in the literature. The optimal treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…Cerebral proliferative angiopathy (CPA), as described by Lasjaunias et al, differs from our case in that CPA is characterized by ''the small caliber of a multitude of feeding arteries and draining veins,'' 6 while our case involves abnormalities of the venous phase only and does not have arteriovenous shunting. More recent reports have also identified arteriovenous fistula, flow-related aneurysm, 7 and intracranial hemorrhage 7,8 in CPA, neither of which were observed in our patient. Leptomeningeal angiomatosis of SWS may have a similar radiographic appearance to our case.…”
Section: Other Entities With Abnormal Network Of Small Veinssupporting
confidence: 59%
“…Cerebral proliferative angiopathy (CPA), as described by Lasjaunias et al, differs from our case in that CPA is characterized by ''the small caliber of a multitude of feeding arteries and draining veins,'' 6 while our case involves abnormalities of the venous phase only and does not have arteriovenous shunting. More recent reports have also identified arteriovenous fistula, flow-related aneurysm, 7 and intracranial hemorrhage 7,8 in CPA, neither of which were observed in our patient. Leptomeningeal angiomatosis of SWS may have a similar radiographic appearance to our case.…”
Section: Other Entities With Abnormal Network Of Small Veinssupporting
confidence: 59%
“…Other findings are the paucity of draining vessels compared with the nidus size, proliferation of pial vessels, and presence of flow void -indicating vigorously flowing blood. The absence of acute infarcts or intracranial hemorrhages also supports this diagnosis, even though they can be present (2,7,10,14,19) .…”
Section: Diagnosismentioning
confidence: 82%
“…When hemorrhage is the target, partial embolization seems to be sufficient. Partial targeted embolization was employed and yielded progressive improvement in the case reported by Giragani et al, 2018, where the source of bleeding could be clearly identified (14) and also in a case series by Lasjaunias et al, 2008 (2) . Conversely, the same procedure aimed at reducing the shunt vascularity lead to symptom recurrence and neurological decline (3) .…”
Section: Treatmentmentioning
confidence: 95%
See 2 more Smart Citations